ATP Induced Brain-Derived Neurotrophic Factor Expression and Release from Osteoarthritis Synovial Fibroblasts Is Mediated by Purinergic Receptor P2X4 - Klein, Kerstin; Aeschlimann, André; Jordan, Suzana; Gay, Renate; Gay, Steffen; Sprott, Haiko (PLOS ONE, 2012)
Brain-derived neurotrophic factor (BDNF), a neuromodulator involved in nociceptive hypersensitivity in the central nervous system, is also expressed in synoviocytes of osteoarthritis (OA) and rheumatoid arthritis (RA) patients. We investigated the role of P2 purinoreceptors in the induction of BDNF expression in synovial fibroblasts (SF) of OA and RA patients. Cultured SF from patients with symptomatic knee OA and RA were stimulated with purinoreceptor agonists ATP, ADP, or UTP. The expression of BDNF mRNA was measured by quantitative TaqMan PCR. BDNF release into cell culture supernatants was monitored by ELISA. P2X4 expression in synovial tissue was detected by immunohistochemistry. Endogenous P2X4 expression was decreased by siRNA transfection before ATP stimulation. Kinase pathways were blocked before ATP stimulation. BDNF mRNA expression levels in OASF were increased 2 h and 5 h after ATP stimulation. Mean BDNF levels in cell culture supernatants of unstimulated OASF and RASF were 19 (±9) and 67 (±49) pg/ml, respectively. BDNF levels in SF supernatants were only elevated 5 h after ATP stimulation. BDNF mRNA expression in OASF was induced both by P2X receptor agonists ATP and ADP, but not by UTP, an agonist of P2Y purinergic receptors. The ATP-induced BDNF mRNA expression in OASF was decreased by siRNA-mediated reduction of endogenous P2X4 levels compared to scrambled controls. Inhibition of p38, but not p44/42 signalling reduced the ATP-mediated BDNF mRNA induction. Here we show a functional role of the purinergic receptor P2X4 and p38 kinase in the ATP-induced expression and release of the neurotrophin BDNF in SF.